Mengembangkan Kesadaran Digital Sehat Pada Siswa Sekolah Dasar Melalui Pemberdayaan Sosialisasi Etika Bermedia Sosial - Gunadharma, Aditya; Anjelina, Anjelina; Prasetyo, Dahlan; Hapsari, Elok Fadinda; Mukaromah, Eti Faidatul; Amalina, Fafa Nurul; Nisa, Ilma Nazihatun; Setianingsih, Lilis; Puspitasari, Melani Indah; Jumani, Nurul Putri Azkiyyah; Setyamien, Salsabila Khairunisa; Subekti, Sigit Waris; Al Islami, Teuku Mohammad Daffa; Rizqy, Wafa Maulana; Futri, Widya Aqilla; Ma`summah, Siti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This community service activity aims to enhance elementary school students’ awareness of healthy digital behavior through the socialization of social media ethics and responsible internet use. The method applied was Participatory Action Research (PAR), involving students, teachers, and school stakeholders in an active, collaborative learning process. The program took place at MI Muhammadiyah, Pagentan District, on August 16, 2025, for three hours, including material presentation, case simulations, educational games, and reflective discussions. The results indicate an increased understanding of digital ethics, the emergence of critical attitudes toward gadget use, and the establishment of a “digital healthy class” commitment between teachers and students. Teachers acted as local leaders to sustain digital literacy values within learning activities. This activity demonstrates that a participatory approach effectively promotes behavioral transformation and fosters a culture of responsible digital awareness among elementary school students.